Measuring macroprudential risk through financial fragility: A Minskyan approach - Éric Tymoigne (Levy Economics Institute of Bard College, 2012)
This paper presents a method to capture the growth of financial fragility within a country and across countries. This is done by focusing on housing finance in the United States, the United Kingdom, and France. Following the theoretical framework developed by Hyman P. Minsky, the paper focuses on the risk of amplification of shock via a debt deflation instead of the risk of a shock per se. Thus, instead of focusing on credit risk, for example, financial fragility is defined in relation to the means used to service debts, given credit risk and all other sources of shocks. The greater the expected reliance on capital gains and debt refinancing to meet debt commitments, the greater the financial fragility, and so the higher the risk of debt deflation induced by a shock if no government intervention occurs. In the context of housing finance, this implies that the growth of subprime lending was not by itself a source of financial fragility; instead, it was the change in the underwriting methods in all sectors of the mortgage markets that created a financial situation favorable to the emergence of a debt deflation. Stated alternatively, when nonprime and prime mortgage lending moved to asset-based lending instead of income-based lending, the financial fragility of the economy grew rapidly.
Keywords: E12; E32; E44; 330; Debt Deflation; Minsky; Financial Fragility; Systemic Risk